2007
DOI: 10.1111/j.1369-1600.2007.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC STUDY: The human protein kinase C gamma gene (PRKCG) as a susceptibility locus for behavioral disinhibition

Abstract: This study explores the association between a highly heritable behavioral disinhibition phenotype and the protein kinase C gamma (PRKCG) gene in an ethnically diverse youth sample from Colorado, USA. The rationale for this study was based on the impulsive behavior and increased ethanol consumption observed in the protein kinase C gamma (PKC-gamma)-deficient mouse model. Two composite behavioral disinhibition phenotypes and their component behavioral scores [conduct disorder, attention-deficit hyperactivity dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…The result is consistent with the conventionally view that variants in the functional region can effect expression of γPKC normally. For example, the study by Schlaepfer et al discovered that rs3745406 polymorphisms of PRKCG was a susceptibility locus for human disease in samples of Caucasian, which also supports the relationship between gene variation and neuropathic disease [16]. Meanwhile, our results demonstrated that γPKC, which encodes by PRKCG gene, played an important role in the central nervous system's transmembrane signal transduction, and the results was accordant with the previous studies [24].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The result is consistent with the conventionally view that variants in the functional region can effect expression of γPKC normally. For example, the study by Schlaepfer et al discovered that rs3745406 polymorphisms of PRKCG was a susceptibility locus for human disease in samples of Caucasian, which also supports the relationship between gene variation and neuropathic disease [16]. Meanwhile, our results demonstrated that γPKC, which encodes by PRKCG gene, played an important role in the central nervous system's transmembrane signal transduction, and the results was accordant with the previous studies [24].…”
Section: Discussionsupporting
confidence: 93%
“…1 Linkage disequilibrium of the 12 tag SNPs in PRKCG gene as a complex process and was not clear, but it was universally acknowledged that environment carcinogens could induce genomic polymorphism, such as oxidative stress, drinking, smoking, and ionizing radiation [9,10]. Previous research found that genetic variants of PRKCG can initiate the onset of homologous diseases, such as behavioral disinhibition, major depressive disorder, and myotonic dystrophy [16,17,24]. Therefore, in the present study, we aimed to study the involvement between five SNPs of PRKCG (rs2547362, rs3745406, rs454006, rs8103851, rs2242245) and risk of osteosarcoma in the ethnically Han Chinese.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The pool of potential subjects encompassed over 5000 youth; we selected for inclusion in this study those assessed between ages 17 and 21 (mean age 18 ± 1.50). A more detailed description of this sample has been published elsewhere (22). A description of the study was presented to all subjects, who signed written informed assent (minors) or consent (adults) to participate.…”
Section: Center For the Genetics Of Antisocial Drug Dependencementioning
confidence: 99%
“…In ADHD, where arousal regulation may be dysfunctional (van der Meere, 2002; O'Connell et al, 2008), this may result in a complex interplay between novelty seeking and hyperactive behaviors in attempting to regulate or optimize arousal levels. However, apart from evidence that both phenotypes contribute to a highly heritable latent trait (Young et al, 2000; Schlaepfer et al, 2007), to our knowledge, studies have yet to address the etiological links between childhood hyperactive–impulsive symptoms and novelty seeking scores in quantitative genetic studies.…”
Section: Introductionmentioning
confidence: 99%